Grand-Maternal Lifestyle During Pregnancy and Anthropometric Characteristics in Adolescence and Young Adulthood: An Intergenerational Cohort Study. (29th May 2020) - Ding, Ming; Strohmaier, Susanne; Schernhammer, Eva; Yuan, Changzheng; Sun, Qi; Michels, Karin; Tamimi, Rulla; Chavarro, Jorge E
Abstract: Objectives: To examine associations of healthy lifestyle during pregnancy with anthropometric characteristics of grandchildren during adolescence and young adulthood. Methods: Our study population included 14, 001 grandmother-mother-child triads comprised of participants of two ongoing prospective cohort studies of related individuals. We used self-reported grand-maternal gestational weight gain (GWG), diet, physical activity, and smoking during pregnancy to create a lifestyle score ranged from 0–12, with a higher score indicating healthier lifestyle. Maternal and grandchild characteristics, including anthropometry, were self-assessed in follow-up questionnaires. Results: Compared with individuals whose grandmothers had the least healthy lifestyle during pregnancy, individuals whose grandmothers had the most healthy lifestyle had 0.17 (95% CI: 0.01, 0.33; P for trend = 0.05) kg/m2 lower body mass index (BMI) and 7% (95% CI: 2%, 12%; P for trend = 0.001) lower risk of overweight or obesity in the offspring during adolescence and young adulthood. The inverse associations between grand-maternal lifestyle and BMI in offspring were mainly mediated by maternal pre-pregnancy BMI (mediation effect: 64%; P value = 0.001). Overall, maternal BMI, along with maternal socioeconomic status and lifestyles in the second and third generations accounted for all of the inter-generational association (mediation effect: 99%; P value < 0.001). The inverse associations between grand-maternal lifestyle and anthropometric characteristics of offspring were not modified by grand-maternal pre-pregnancy BMI, grandchild age, or grandchild gender. Conclusions: Grandchildren of women who had the healthiest lifestyles during pregnancy defined by no excess gestational weight gain, no smoking, a healthy diet and being physically active, were less likely to be overweight or obese in adolescence through early adulthood. Funding Sources: Supported by National Institutes of Health grants U01-HL145386, UM1-CA176726, P30-DK046200, U54-CA155626, HD066963, HL096905, DK084001 and MH087786.